Hepatic and renal functions of paediatric patients with thalassaemia: a cross-sectional study from two large thalassaemia centres in Sri Lanka - Meranthi Fernando; Anuja Premawardhena; Sachith Mettananda; Hashan Pathiraja; Wasana Wijenayake; Raveen Thennakoon; Dayananda Bandara; Roshitha De Silva (BMJ Open)
Objectives Thalassaemia is a genetic disorder of haemoglobin synthesis characterised by life-long chronic anaemia. Although the endocrine and cardiac complications of thalassaemia are well-studied, hepatic and renal complications are understudied. This study aims to describe the hepatic and renal functions and to understand their determinants among paediatric patients with β-thalassaemia.Design Cross-sectional study.Setting Two largest thalassaemia centres in Sri Lanka.Participants All haematologically confirmed patients with β-thalassaemia aged 1–16 years attending the study sites were recruited between 1 January and 31 March 2023. Data were collected by interviewing parents and patients, performing physical examinations and perusing clinical records.Results 72 children (girls 52.8%) were recruited. The mean age was 7.3 years (SD 3.8). A majority (44 (61.1%)) had β-thalassaemia major, while 22 (30.6%) had haemoglobin E β-thalassaemia. 55 children (76.4%) were transfusion dependent. Hepatomegaly was found in 47 (65.3%), while 28 (38.9%) had elevations of both alanine and aspartate transaminases. Haemoglobin E β-thalassaemia type (OR 13.6, 95% CI 2.0 to 92, p=0.008) and high ferritin above 1000 ng/mL (OR 6.2, 95% CI 1.0 to 38, p=0.047) were independent factors associated with high transaminases. 11 (15.5%) patients had an estimated glomerular filtration rate (eGFR) below 90 mL/min. The proportion of children with low eGFR was higher in β-thalassaemia major (23.3%), transfusion-dependent (18.5%) and deferasirox treatment (18.5%) groups.Conclusions Elevation of hepatic transaminases is common among children with thalassaemia, especially among the subset of patients with haemoglobin E β-thalassaemia and those with high ferritin. Milder reductions in eGFR are noted in some patients with transfusion-dependent β-thalassaemia major.